Pengaruh Layanan Pesan Antar (Delivery Order) Grabfood terhadap Omzet Bisnis Kuliner di Kecamatan Teluk Segara - Randi Engga Putra; Sazili; Ade Irma Suryani (Jurnal Ilmiah Aset, 2026)
Digital platforms such as GrabFood have become an effective solution to support today's fast-paced lifestyle. GrabFood has attracted many culinary businesses, including those in Teluk Segara District, an area experiencing rapid culinary business growth. This service is expected to increase the number of orders through wider customer reach, although service fees and business competition may affect profits. This study aimed to examine the effect of GrabFood delivery services on the turnover of culinary businesses in Teluk Segara District. The study employed a quantitative approach with a causal associative method. Data were collected through questionnaires distributed to Grab partner businesses. The results showed that GrabFood delivery services had a positive and significant effect on culinary business turnover. The partial t-test produced a significance value of 0.013, which was lower than 0.05, and a t-value of 2.651, exceeding the t-table value of 2.045. Furthermore, the simple linear regression equation was obtained as Y = 16.599 + 0.321X, indicating a positive relationship between GrabFood delivery services and culinary business turnover. Therefore, GrabFood delivery services significantly contribute to increasing culinary business turnover in Teluk Segara District.